Application of ultraviolet light as an indoor disinfectant - Khair, Hafizhul; Suryati, Isra; Utami, Rahmi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
WHO announced a new outbreak disease, COVID-19, as a public health emergency that has plagued the world since January 30, 2020. Critical readiness and response are needed, such as equipping healthcare workers and facility management with important information, procedures, and tools to be safe and working effectively in responding to the outbreak. One of the critical hospital's services facilities is an isolation room/inpatient room. This room needs to be sterilized using a disinfectant regularly. The use of disinfectants, such as chemical fluids can only kill vegetative cells from microbes/viruses. Microbes/viruses, especially in the form of vegetative cells, could be killed by ultraviolet exposure. The objectives of this service program are: (1) Improving the cleanliness of hospital inpatient rooms so that they can be used immediately in treating patients (2) Speeding up the process of cleaning/sterilizing hospital inpatient rooms/isolation given the increasing number of patients in monitoring for covid-19 cases. The problem with inpatient sanitation/isolation in hospitals is usually many microbes in the indoor air. Clean and sterile inpatient/isolation rooms are needed in the patient's care. Therefore, it is necessary to improve the process of cleaning /sterilizing the inpatient room/isolation in the hospital by using UV exposure.